Sex-specific photosynthetic capacity and Na+ homeostasis in Populus euphratica exposed to NaCl stress and AMF inoculation - Wu, Na; Li, Zhen; Wu, Fei; Zhen, Lina (Frontiers in Plant Science, 2022)
Soil salinity and associated land degradation are major ecological problems. Excess Na+ ions in soil impede the plant photosynthetic process and Na+ homeostasis status. Arbuscular mycorrhizal fungi (AMF) can alleviate salt stress in host plants. Although a number of studies have demonstrated that Na+ accumulation is decreased by mycorrhizae, the molecular mechanisms involved have received little attention from researchers. Populus euphratica is a typical natural woody tree with excellent salt tolerance. Due to its symbiosis forming capability with AMF, we explored the influence of Funneliformis mosseae on the growth, photosynthesis, and expression of three genes involved in Na+ homeostasis within dioecious P. euphratica under salt stress. The results indicated that salt stress significantly increases Na+ contents and inhibits growth status and photosynthetic capacity, especially in females. However, AMF had positive effects on the growth status, photosynthetic capacity and Na+ homeostasis, especially in males. The expression levels of NHX1 in shoots and HKT1 and SOS1 in roots, all of which are involved in Na+ homeostasis, were upregulated by F. mosseae under salt stress. For males, the beneficial effect of AMF centered on extruding, sequestering and long-distance transporting of Na+ ions. For females, the beneficial effect of AMF centered on extruding excessive Na+.